Effect of Instructional Animation on Pupils’ Academic Performance in Literacy - Azeez Arisekola SALMAN (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the persistent problem of low literacy performance among primary school pupils in Nigeria, which is often attributed to teacher-centered instructional methods and limited use of technology in classrooms. The purpose of the research was to examine the effect of instructional animation on pupils’ academic performance in literacy, with specific attention to gender and school type. The study involved 95 pupils from four selected public and private primary schools in Ilorin West Local Government Area of Kwara State, consisting of 53 pupils from public schools and 42 from private schools. A pre-test, post-test, non-equivalent control group quasi-experimental design with a 2×2×2 factorial structure was adopted for the study. Data were collected using the Pupils’ Literacy Performance Test (PLPT), the Instructional Guide for Instructional Animation (IGIA), and the Instructional Guide for Conventional Method (IGCM). The instruments were validated by experts and the PLPT yielded a reliability coefficient of 0.74. Data obtained were analyzed using Analysis of Variance (ANOVA) to test the main and interaction effects of instructional animation, gender, and school type on pupils’ literacy performance. The findings revealed that instructional animation had a significant positive effect on pupils’ academic performance in literacy, as those taught with animation outperformed their peers taught with the conventional method. However, there were no significant interaction effects among instructional animation, gender, and school type, indicating that the strategy was effective and inclusive across different learner groups. The study concludes that integrating instructional animation into literacy instruction can enhance pupils’ learning outcomes and promote equitable, technology-based education in primary schools.